Pre‐existing immunity to SARS‐CoV‐2 associates with strong T cell responses induced by inactivated COVID‐19 vaccines. Issue 3 (20th March 2023) - Yi, Xuan; Wang, Yuhao; Li, Quanrun; Li, Xiaoyi; Zhang, Panli; Fu, Xin; Gu, Shuqin; Zhang, Daqian; Liu, Xiaoyi; Lou, Haonan; Wu, Yuemei; Tang, Libo; et al.
Abstract: Individuals with a recent common cold coronavirus infection, which leads to pre‐existing immunity against SARS‐CoV‐2, displayed a less severe course of COVID‐19. However, the relationship between pre‐existing immunity against SARS‐CoV‐2 and the inactivated‐vaccine‐induced immune response is still unknown. Here, 31 healthcare workers who received standard two doses of inactivated COVID‐19 vaccines (Weeks 0 and 4, respectively) were enrolled, vaccine‐induced neutralization and T cell responses were detected, and the correlation between the pre‐existing SARS‐CoV‐2‐specific immunity was analyzed. We found the SARS‐CoV‐2‐specific antibodies, pseudovirus neutralization test (pVNT) titers, and spike‐specific interferon gamma (IFN‐γ) production in CD4 + and CD8 + T cells were significantly elevated after two doses of inactivated vaccines. Interestingly, the pVNT titers after the second dose of vaccination displayed no significant correlation with the pre‐existing SARS‐CoV‐2‐specific antibodies or B cells, nor the pre‐existing spike‐specific CD4 + T cells. Notably, the spike‐specific T cell response after the second dose of vaccination was positively correlated with the pre‐existing receptor binding domain (RBD)‐specific B cells and CD4 + T cells, which were documented by the frequencies of RBD‐binding B cells, the breadth of RBD‐specific B cell epitopes, and the frequency of IFN‐γ‐expressing RBD‐specific CD4 + T cells. Overall, the inactivated‐vaccine‐induced T cell responses, not the inactivated‐vaccine‐induced neutralization, closely correlated with pre‐existing immunity to SARS‐CoV‐2. Our results provide a better understanding of inactivated‐vaccine‐induced immunity and help predict the immunogenicity induced by inactivated vaccines in individuals.